Pelatihan Pengolahan dan Pengemasan Keripik Buah - Wanadiatri, Halia; Juniawan, Alvin; Fathurrahman, Fathurrahman; Wedowati, Endang Retno; Rejeki, Fungki Sri; Haryanta, Dwi (LPPM Universitas Bumigora, 2024)
The purpose of this community service is to provide solutions through providing tools and training for processing and packaging fruit chips in Gelangsar Village, Gunungsari, West Lombok. This training activity is one of Kosabangsa's programs for 2023. Participants in this training consist of village owned enterprises and farmer groups totalling 26 people. The method used in this service is socialization and training related to technology and innovation in processing and packaging fruit chips. The results of implementing community service through questions and answers and discussions are that the community strongly agrees with the training on processing and packaging fruit chips because it can increase understanding, skills and new, more innovative business ideas to improve the economy of Gelangsar village residents. Through this training, the community has new insights regarding the latest technology and innovation in processing chips from post-harvest fruit and packaging them so that they are durable and long-lasting. The continuation of this program is related to product marketing assistance which will collaborate with various related parties such as Business and Technology Incubator of Universitas Islam Al-Azhar and Nusa Tenggara Barat Mall. The impact of this program is the local people are able to increase their income through the training.